Macroprudential policy and the role of institutional investors in housing markets - Manuel A. Mu\~noz; Frank Smets (European Systemic Risk Board (ESRB), European System of Financial Supervision, 2022)
Since the onset of the Global Financial Crisis, the presence of institutional investors in housing markets has steadily increased over time. Real estate funds (REIFs) and other housing investment Örms leverage large-scale buy-to-rent real estate investments that enable them to set prices in rental markets. A signiÖcant fraction of this funding is being provided in the form of non-bank lending - which is not subject to regulatory LTV ratios - and REIFs are generally not constrained by leverage limits. We develop a quantitative DSGE model that incorporates the main features of the REIF industry and identify leakages of existing macroprudential policy: (i) already existing countercyclical LTV rules on residential mortgages trigger a credit reallocation towards the REIF sector that can amplify Önancial and business cycles; while (ii) "non-existent" countercyclical LTV rules on lending to REIFs are particularly eective in taming such cycles. Due to the dierent mechanisms through which they operate, both types of LTV rules complement each other and jointly yield larger welfare gains (for savers and borrowers) than in isolation.
Keywords: E44; G23; G28; 330; rental housing; real estate funds; loan-to-value ratios; leverage; leakages